NIR-Triggered Synergic Photo-chemothermal Therapy Delivered by Reduced Graphene Oxide/Carbon/Mesoporous Silica Nanocookies - Chen, Yu-Wei; Chen, Po-Jung; Hu, Shang-Hsiu; Chen, I-Wei; Chen, San-Yuan (Advanced functional materials, 2014)
A novel photo‐responsive drug carrier that doubles as a photothermal agent with a nanocookie‐like structure is constructed by coating amorphous carbon on a mesoporous silica support self‐assembled on a sheet of reduced graphene oxide. With a large payload (0.88 mmolg−1) of a hydrophobic anticancer drug, (S)‐(+)‐camptothecin (CPT), nanocookies simultaneously provide a burst‐like drug release and intense heat upon near‐infrared exposure. Being biocompatible yet with a high efficiency for cell uptake, nanocookies have successfully eradicated subcutaneous tumors in 14 days following a single 5 min NIR irradiation without distal damage. These results demonstrate that the nanocookie is an excellent new delivery platform for local, on‐demand, NIR‐responsive, combined chemotherapy/hyperthermia for tumor treatment and other biomedical applications. Formed by a one‐pot, scalable emulsion method and triggered by near infrared irradiation, photosensitive nanoparticles with a silica/carbon nanostructure supported on a reduced graphene oxide substrate can control release of hydrophobic chemotherapy drugs with synergistic hyperthermia effects, eradicating tumor cells in vivo and in vitro on demand.